Solve for x over the reals:
lo g 3 ( lo g 2 ( lo g 3 ( x ) ) = 0
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
i also solved in the same way. because logarithm is defined as a number to which base is raised to the power
lo g 3 ( lo g 2 ( lo g 3 ( x ) ) = 0 ⟹ lo g 3 ( lo g 2 ( lo g 3 ( x ) ) = lo g 3 ( 1 ) ⟹ lo g 2 ( lo g 3 ( x ) ) = 1 ⟹ lo g 2 ( lo g 3 ( x ) ) = lo g 2 ( 2 ) ⟹ lo g 3 ( x ) = 2 ⟹ x = 3 2 ⟹ x = 9
Therefore, x equals 9
first, change the first logarithm with a base of 3 into exponential form. The result will be like this.
then, do the same process to second logarithm. and it will be like this.
with that, you can now get the value of x by changing it into exponential form again and came up with the answer x = 9.
Problem Loading...
Note Loading...
Set Loading...
lo g 3 ( lo g 2 ( lo g 3 x ) ) = 0
⟹ 3 0 = lo g 2 ( lo g 3 x )
⟹ 2 1 = lo g 3 x
⟹ x = 3 2 = 9